Quantitative Analysis of Water Infiltration in Soil Cores Using X‐Ray - Weller, U. (2020)
X‐ray radiography is a suitable approach to study water dynamics in undisturbed soil. However, beam hardening impairs the deduction of soil moisture changes from X‐ray attenuation, especially when studying infiltration of water into cylindrical soil columns. We developed a calibration protocol to correct for beam hardening effects that enables the quantitative determination of changing average water content in two‐dimensional projections. The method works for a broad range of materials and is easy to implement. Moreover, we studied the drift of X‐ray attenuation values due to the detector latency and eliminated its contribution to the quantitative analysis. Finally we could visualize the dynamics of infiltrating water into undisturbed cylindrical soil samples.